A Model for Enhancing the Environmental Performance by Integrating Lean and Green Productivity Concept: A Case Study of Food Production - Hanun, Nur Ravita; Cahyana, Atikha Sidhi; Wulandari, Indah Apriliana Sari (Jurnal Teknik Industri, 2024)
The increase in food production activities has led to a significant decline in the environmental quality, particularly affecting the surrounding river systems. This research addresses the need to identify and minimize various types of waste by integrating Lean and Green productivity concepts. The main objective is to reduce non-value-added (NVA) activities that contribute to both environmental degradation and inefficiencies in production. The study applies the Lean framework to identify seven types of waste in food production while also addressing green waste, such as excessive material use and energy consumption. Green Integration Value Stream Mapping (GIVSM) is utilized to assess the current state of value-added (VA) activities and to simulate improvements for future production systems. The initial analysis reveals a low VA of 1.5 hours due to inefficient customer information flow and prolonged loading times. Improvements are implemented by shifting the information system from a push to a pull strategy, significantly reducing production time and lowering both Lean and Green waste. The results demonstrate that integrating these concepts can enhance environmental performance and operational efficiency. This study provides valuable insights for food production companies seeking to balance productivity and sustainability.